The Development of Reference Book from Medicinal Plant Exploration Results in Rote Tengah Sub-district, Rote Ndao District - SonyaSonya Titin M. Nge; Apriliana Ballo; Alan Ch. Sabuna; Anggreini D.N. Rupidara; Arnold Ch. Hendrik (Postgraduate, University of Mataram, 2024)
The utilization of medicinal plants has become one alternative for communities to treat illnesses. This is because the use of medicinal plants, besides being relatively affordable, also does not cause side effects compared to the use of modern medicine or chemical-based drugs. This study aims to develop a reference book of medicinal plants in Rote Tengah Sub-district, Rote Ndao District. The development model used in this research is the ADDIE model (analysis, design, development, implementation, evaluation). The research results obtained from material expert testing showed a validity of 94.6%, design expert testing showed 95.5%, and media expert testing showed 100%. Overall, the percentage of assessments from all three experts indicates a value of 96.7% with a qualification of very valid (highly appropriate). This indicates a positive response to the developed medicinal plant reference book, which is deemed suitable for use as a learning resource. This is because the developed medicinal plant reference book has its own advantages, where the illustrations in the reference book are made with attractive designs, thus attracting students' attention and making it easier to understand